ANALISIS TINGKAT BAHAYA EROSI DARI VEGETASI ALANG-ALANG PADA BERBAGAI KELERENGAN DI SUB DAS BATI-BATI (DAS MALUKA) KALIMANTAN SELATAN - Zainal Abidin; Syarifuddin Kadir; Eko Rini Indriyatie (Jurnal Sylva Scienteae, 2022)
The type of land cover affects the level of erosion hazard in an area. The purpose of this study was to analyze the amount of erosion hazard and determine the level of erosion hazard (TBE) on the reed vegetation on various slopes in the Bati-bati sub-watershed of the Maluka watershed, South Kalimantan. Sampling of data using purposive sampling technique. Samples were taken as many as 6 land units based on vegetation, soil type, reed land cover and slope class, which were obtained from the map overlay of land units. Each sample point was taken soil samples using a sample ring to be tested in the laboratory. Then, the data were analyzed using Universal Soil Loss Equation (USLE) and Erosion Hazard Analysis (TBE). The highest number of erosion values occurred in reed Land Unit (UL) 39 with a slope of 15-25% with an erosion value of 130.96 tons/ha/year, while the lowest erosion value was found in UL 34 with a slope of 0-8 and erosion of 9.64 tons/ha/year. The erosion hazard level of the land unit under study shows the percentage of light grade (IR) occurring at UL7, UL 34, UL 50 and UL 59 with a flat slope (0-8), while the medium grade (II-S) occurs at UL. 37 with gentle slopes (8-15) and UL 39 with steep slopes (25-40)Jenis penutupan lahan berpengaruh terhadap tingkat bahaya erosi dalam suatu wilayah. Tujuan dari penelitian ini ialah menganalisis jumlah bahaya erosi dan menentukan adanya tingkat bahaya erosi (TBE) pada vegetasi alang-alang pada berbagai kelerengan di sub DAS Bati-bati DAS Maluka, Kalimantan Selatan. Pengambilan sampel data menggunakan teknik purposive sampling. Sampel diambil sebanyak 6 unit lahan berdasarkan vegetasi, jenis tanah, tutupan lahan alang-alang dan kelas kelerengan, yang didapat dari overlay peta satuan lahan. Setiap titik sampel diambil sampel tanahnya menggunakan ring sampel untuk diuji di laboratorium. Kemudian, data dianalisis menggunakan persamaan Universal Soil Loss Equation (USLE) dan Analisis Tingkat Bahaya Erosi (TBE). Jumlah nilai  erosi tertinggi terjadi pada Unit Lahan Alang-Alang (UL) 39 dengan kemiringan lereng 15-25% dengan nilai erosi sebesar130,96 ton/ha/thn, sedangkan nilai erosi terendah terdapat pada UL 34 dengan kemiringan lereng 0-8 dan nilai erosi sebesar 9,64 ton/ha/thn. Tingkat bahaya erosi dari unit lahan yang diteliti menunjukkan persentase kelas ringan (I-R) terjadi pada UL7, UL 34, UL 50 dan UL 59 dengan kemiringan lereng yang datar (0-8), sedangkan pada kelas sedang (II-S) terjadi pada UL 37 dengan kemiringan lereng landai (8-15) dan UL 39 dengan  kemiringan lereng curam (25-40).